2018
DOI: 10.1016/j.jmbbm.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain stiffens post mortem

Abstract: Alterations in brain rheology are increasingly recognized as a diagnostic marker for various neurological conditions. Magnetic resonance elastography now allows us to assess brain rheology repeatably, reproducibly, and non-invasively in vivo. Recent elastography studies suggest that brain stiffness decreases one percent per year during normal aging, and is significantly reduced in Alzheimer's disease and multiple sclerosis. While existing studies successfully compare brain stiffnesses across different populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 81 publications
(143 reference statements)
3
69
0
Order By: Relevance
“…Gefen and Margulies, for instance, showed that the mechanical properties of brain tissue in vivo differ from excised tissue only after repetitive, but not at the first indentation [48]. Weickenmeier et al used magnetic resonance elastography and showed that brain tissue rapidly stiffens after death [49]. As it is currently unclear how in vivo mechanical properties change post mortem, mechanical tissue properties must be measured in vivo to rule out any effects elicited by the death of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Gefen and Margulies, for instance, showed that the mechanical properties of brain tissue in vivo differ from excised tissue only after repetitive, but not at the first indentation [48]. Weickenmeier et al used magnetic resonance elastography and showed that brain tissue rapidly stiffens after death [49]. As it is currently unclear how in vivo mechanical properties change post mortem, mechanical tissue properties must be measured in vivo to rule out any effects elicited by the death of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…When the brain is presumed rigid, our simulations show that the peak pressures in the PVS during pulsations can reach 3 mmHg (Fig 2c). Given that the brain is a soft tissue with a shear modulus in the range of 1-8 kPa [16][17][18][19] , we estimated that the peak displacement of the brain tissue induced by the pressure profile in Fig 2c would be 0.64m (with a shear modulus of 4 kPa). This displacement value stands in stark contrast to the fact that the arterial wall displacement driving the flow is only 0.06m.…”
Section: Ignoring Brain Deformability Leads To Implausibly High Pressmentioning
confidence: 99%
“…The radius of the simulated section of brain tissue was taken to be in the range of 100-200 m, half of the typical distance between two penetrating arteries in the mouse cortex 84,85 . The elastic (shear) modulus of the brain tissue is taken to be between 1-8 kPa, spanning the values found in the literature [16][17][18][19]71,72,86,87 .…”
Section: Model Parametersmentioning
confidence: 99%
See 2 more Smart Citations